PENGGUNAAN MEDIA MENTION (MENSTRUAL EDUCATION) UNTUK MENINGKATKAN KEMAMAPUAN BINA DIRI ANAK TUNARUNGU - Ayu Diana; Dedi Mulia; Hadiroh Hadiroh; Jumotul Aqobah; Risma Febrianti (Jurusan Pendidikan Luar Biasa, FKIP Universitas Sultan Ageng Tirtayasa, 2019)
ABSTRACTThe use of Media Mention (Menstrual Education) is used as a medium for menstrual learning and to improve the ability of self-development as well as cognitive of children. In this media trial, the media created has been adapted to the needs of the child. So that the implementation of the media can be accepted by children and function properly in accordance with the use and purpose of the use of these media. The purpose of this media trial is to determine the effectiveness of the use of mention media (menstrual education) in improving the ability of self-development of Deaf children in SKh 01 Pembina Pandeglang. The method used in this trial is to use the experimental method in the form of Pre-Experimental Design. Based on the results of the trial, the use of mention media (menstrual education) can improve the ability of self-development of children. This is seen from the progress of the child in the first trial, the second trial, and the third trial where the child experienced an increase in the ability to develop self and count. Thus it can be concluded that the use of Media Mention (Menstrual Education) can improve the ability of self-development.